(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The design of moored floating wave energy converters (WECs) must take into account extreme responses and mooring line loads in order to ensure their survival and continued wave power generation in the ocean environment. This study focuses on Mocean Energy’s hinged raft WEC and aims to provide a comprehensive understanding of its hydrodynamic characteristics in survival wave conditions. To achieve this, a physical model study was conducted on a Froude scale of 1 in 50 at the FloWave Ocean Energy Research Facility, University of Edinburgh. The experiments involved the use of NewWaves focusing of crest and trough at the model hinge location, as well as long irregular waves. Motion responses of the fore and aft bodies of the WEC were measured using a Qualisys camera, and single component load cells were used to measure the forces in the 3-point catenary mooring line. The hydrodynamic characteristics of the WEC were evaluated in terms of response amplitude operators and non-dimensional mooring line loads. Results indicate that the fore and aft bodies of the WEC exhibit similar motion responses, except for the pitch motion. The aft body has a pitch response 2 to 3 times higher than the fore body. Concerning the moorings, the wave load on the mooring line in line with the wave direction was found to be higher than the other two mooring lines which were arranged at an angle to the wave direction. In this paper, a brief discussion of the model set-up, parameters, test procedure, analysis of results, and discussion will be reported. The results will provide insight into the behaviour of the Mocean device in survival wave conditions and will aid with the determination of appropriate design parameters for optimal performance and survival in the ocean environment.